LEARNING QUALITY ASSURANCE MANAGEMENT IN MADRASAH ALIYAH AL-IHSAN TANAH GROGOT - Muhammad Yuseran; Nunuk Repiatun (Berajah Journal, 2023)
Implementation of internal quality assurance as a form of quality improvement that leads to improved service and customer satisfaction. This quality assurance is carried out in guaranteeing the learning program to be able to meet or exceed the quality standards that have been set, and to be able to achieve the vision, mission, goals and strategic plans that have been set or prepared. The aim of the study was to determine the quality assurance management of learning at Madrasah Aliyah Al-Ihsan Tanah Grogot and to find out the factors that influence the quality assurance management of learning at Madrasah Aliyah Al-Ihsan Tanah Grogot. This research uses a qualitative approach with a descriptive type. Data obtained through interviews, documentation and observation. Head of madrasa, deputy head of madrasa; curriculum field; student; facilities and infrastructure as well as school administrative staff as the main data source and teachers, parents and students as additional data sources. Madrasah Aliyah Al-Ihsan Tanah Grogot has implemented learning quality assurance management which can be seen from 4 cycles of quality assurance, namely first, mapping in which the madrasa realizes its vision, mission and goals, by compiling annual programs, semester programs, madrasah work plans for quality improvement. Second, fulfillment by implementing the madrasah work plan in improving quality. Third, control by conducting continuous evaluations to improve the quality of education in the planning and implementation process and finally follow-up. The factors that influence the improvement of the quality of education are leadership and management, curriculum, teachers and learning processes, student input, student facilities and the learning environment.